High seas in the cloud: the role of big data and artificial intelligence in support of high seas governance – The Sargasso Sea pilot - David Freestone; Kieran N. Bjergstrom; Kristina M. Gjerde; Patrick Halpin; Kevin P. Fleming; Andrew Hudson; Alex D. Rogers; Fae Sapsford; Vardis M. Tsontos; Jorge Vazquez-Cuervo; David Vousden (Frontiers in Marine Science, 2024)
This article examines the future governance of areas beyond national jurisdiction (ABNJ) in the wake of the new 2023 United Nations Agreement using the work on the Sargasso Sea as a prototype. After discussing the legal framework and current challenges facing the ABNJ regime, some details are provided on open ocean data collection technologies, including big data and artificial intelligence (AI), used in support of ocean governance. Based on a technology-enabled ocean governance cycle, the role that data, information technology and data-science can play in incorporating empirical scientific knowledge into policy and decision-making is examined with a focus on the open ocean. The article concludes with a vision of future high seas governance based on the 2023 Agreement and how big data and AI can play a crucial role in meeting the exciting challenges that the new agreement poses.

The Sargasso Sea High Seas EBSA After Ten Years: Is It Still Relevant and How Has It Helped Conservation Efforts? - Howard S. J. Roe; David Freestone; Fae Sapsford (Frontiers in Marine Science, 2022)
The Sargasso Sea is a high seas ecosystem located within the North Atlantic Subtropical Gyre. The floating Sargassum macroalgae for which it is named support a diverse and productive ocean ecosystem. The floating mats and windrows of S argassum house distinct communities of animals including endemic species, and provide shelter, nursery areas and food for many others including juvenile turtles, fish, and birds. A decade ago, in 2012, the two million square mile core area of the Sargasso Sea was “described” by the parties to the Convention on Biological Diversity (CBD) as an Ecologically or Biologically Significant Marine Area (EBSA), having scored highly on six of the seven designated criteria. At the time it was the largest high seas EBSA to be so described. This paper reviews the scientific evidence supporting the finding that it meets the rigorous criteria for an EBSA and assesses whether there have been major changes in the decade since. It puts this in the context of the work of the Sargasso Sea Commission and the Hamilton Declaration Signatories to “conserve the Sargasso Sea for the benefit of present and future generations” and assesses the extent to which being an EBSA has assisted with these conservation efforts.

The Sargasso Sea Commission: An Evolving New Paradigm for High Seas Ecosystem Governance? - David Freestone (Frontiers in Marine Science, 2021)
The Sargasso Sea is to be found within the North Atlantic Subtropical Gyre. Its borders are the major ocean currents. These boundaries shift with these currents, but there is a core area that covers approximately 2 million square nautical miles situated around the Bermuda archipelago, the majority of which is beyond the national jurisdiction of any State. Ten governments have now signed the 2014 Hamilton Declaration on Collaboration for the Conservation of the Sargasso Sea, which mandated the Government of Bermuda to appoint the members of the Sargasso Sea Commission—the first such body to take on a stewardship role for a high seas ecosystem. The Commission has committed to working with the existing international organizations with jurisdictional competences over a myriad of high seas activities. This paper will examine the work of the Commission and lessons learned over the past decade; it will discuss its possible role as a “boundary spanning” organization and look forward to its future in the light of recent grants from the Global Environment Facility (GEF) and the Fonds Francais pour l’Environnement Mondial (FFEM).

A role for artificial night-time lighting in long-term changes in populations of 100 widespread macro-moths in UK and Ireland: a citizen-science study - John Fawcett Wilson; David Baker; Janet Cheney; Mike Cook; Martin Ellis; Roger Freestone; David Gardner; Graham Geen; Robin Hemming; Don Hodgers; Stephen Howarth; Ade Jupp; et al. (Journal of Insect Conservation, 2018)

Climate association with fluctuation in annual abundance of fifty widely distributed moths in England and Wales: a citizen-science study - John Fawcett Wilson; David Baker; Mike Cook; George Davis; Roger Freestone; David Gardner; Dave Grundy; Norman Lowe; Steve Orridge; Heather Young (Journal of Insect Conservation, 2015)